Evaluation of the National Adherence Guidelines for Chronic Diseases in South Africa Using Routinely Collected Data : First Enrollment Report - World Bank (World Bank, Washington, DC, 2019)
This report describes enrollment into the cohorts for protocol 1 for the Evaluation of the National Adherence Guidelines for Chronic Diseases in South Africa Using Routinely Collected Data. The study is evaluating short-term and long-term effects of five interventions being implemented by the National Department of Health (NDoH) in South Africa to improve adherence to HIV care and chronic disease care in general: Fast track initiation counselling, decentralized medicine delivery, adherence clubs, early patient tracing and enhanced adherence counselling. The study uses a randomized evaluation design to compare sites where the intervention was rolled out with control sites providing standard of care. Enrollment began in June 2016 and was uneven in time and by province, as expected in a process using routine data and relying on programmatic implementation. Enrollment of HIV clients into cohorts will enable the NDoH to understand the short-term and long-term impacts of interventions to improve HIV treatment initiation, adherence and retention in care.